The family Fletcher takes Rock Island - Levy, Dana Alison (Delacorte Press, 2016)
Summertime brings the Fletcher Family back to Rock Island where the good times never end, but this summer the boys' favorite lighthouse is all boarded up and with the help from their new neighbors, the Garcia girls, the boys are determined to find out what is really happening with their lighthouse and saving it, no matter what the cost.